Effective remote staff training of objective session notes. Issue 1 (3rd November 2020) - Piazza, Jessica L.; Leaf, Justin B.; Lanier, Lauren L.
Abstract : Session notes are a required component of documenting behavior analytic sessions. The direct training of writing objective session notes is important to the success of direct line staff completing adequate documentation and meeting requirements set forth by agencies, certification boards, and insurance funders. However, in‐person training is not always immediately available due to contextual restrictions. This study evaluated the effectiveness of implementing the teaching interaction procedure when training staff remotely to objectively document client progress within session notes. Three Registered Behavior Technicians™ (RBT®s) were trained via telehealth to complete session notes objectively. Results showed that all 3 participants met the mastery criterion during probes measuring the objective documentation of home‐based behavior analytic sessions. These findings suggest that a training package, such as the teaching interaction procedure, can be effectively implemented remotely when conducting staff training.